Impact of Human Capital on the Organization’s Innovative Capabilities: Case of Telecom Sector in Pakistan - Khan, Samar Hayat; ., Abdul Majid; ., Muhammad Yasir (Information Management and Business Review, 2014)
The purpose of this study is to investigate the impact of human capital on organization’s innovative capabilities in the narrative context of Pakistan. Today various organizations recognized the significance and importance of the intellectual capital. Without any doubt in knowledge-intensive organizations like telecom sector organizations intellectual capital plays a vital role in the contemporary aggressive and everchallenging business environment. The organizations can achieve competitive edge over its competitors by mean of innovation. By effective utilization of intellectual capital organizations can enhance innovative capabilities. Intellectual capital can be classified into three classifications named as human capital, structural capital and relational capital. Human capital is the main component of the intellectual capital and considered as a main aspect for the organization in order to perform in this diverse and unpredictable business environment. The conception of human capital now became mainstream issue for both academics and business practitioner all around the world. However, in the context of developing countries like Pakistan concept of human capital is still under explored. In this study at hand the impact of human capital organization’s innovative capabilities i.e. radical and incremental innovative capabilities are examined. Three hypotheses were developed in order to test the relationship between human capital and innovative capabilities of telecom sector organization in Pakistan. To accomplish the objectives of this study survey method was used in which data was collected through questionnaire. Telecom Sector of Pakistan has been taken as unit of analysis. The collected data was analyzed with the help of SPSS by applying the correlation and regression test. Results of correlation and regression analysis showed that there is a strong relationship between human capital and organization’s innovative capabilities in telecom sector of Pakistan and all three developed hypotheses were supported.